Long-term Follow-up and Muscle Imaging Findings in Brachio-Cervical Inflammatory Myopathy. Issue 4 (July 2021) - Lucchini, Matteo; Bortolani, Sara; Monforte, Mauro; Papacci, Manuela; Ricci, Enzo; Mirabella, Massimiliano; Tasca, Giorgio
Abstract : Objective: To report on a cohort of patients diagnosed with brachio-cervical inflammatory myopathy (BCIM), with specific focus on muscle MRI and follow-up data. Methods: Clinical, histopathologic, serologic, and pre- and post-treatment MRI findings of patients diagnosed with BCIM were retrospectively evaluated. Results: Six patients, all females with a mean age at onset of 53 years (range 37–62 years), were identified. Mean diagnostic delay was 17 months, and mean follow-up was 35 months. Most common clinical features encompassed predominant involvement of neck and proximal upper limb muscles, followed by distal upper limb, facial, and bulbar muscle weakness with different severity. Lower limb involvement was rare, although present in severe cases. Muscle biopsies showed a heterogeneous degree of perivascular and endomysial inflammatory changes. Myositis-specific antibodies were absent in all patients, whereas all resulted positive for antinuclear antibodies; half of the patients had anti–acetylcholine receptor antibodies without evidence of muscle fatigability. MRI showed disproportionate involvement of upper girdle and neck muscles compared with lower limbs, with frequent hyperintensities on short-tau inversion recovery sequences. Partial clinical and radiologic improvement with steroid and immunosuppressant therapy was obtained in most patients, especially in proximal upper limb muscles, whereas neck weakness persisted. Conclusion: BCIM is an inflammatory myopathy with a peculiar clinical and radiologic presentation and a relatively broad spectrum of severity. Long-term follow-up data suggest that appropriate and early treatment can prevent chronic muscle function impairment. MRI characterization can be helpful in reducing diagnostic and treatment delay with positive consequence on clinical outcome.